2009
DOI: 10.1002/msj.20113
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Concepts in the Pathophysiology of Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes mellitus is a multifactorial metabolic disorder. It is characterized by chronic hyperglycemia, insulin resistance, and a relative insulin secretion defect. The prevalence of type 2 diabetes mellitus has risen worldwide in large part because of an increase in obesity and sedentary lifestyles. The underlying pathophysiology and complications of type 2 diabetes mellitus are still being elucidated. Recent advances in diabetes research have helped us to gain a better understanding about insulin resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 91 publications
0
30
0
3
Order By: Relevance
“…IR is a subnormal biological response to a given concentration of insulin [87] in adipose, muscle, and liver cells [68]. This, for instance, results in the overproduction of glucose by the liver despite fasting hyperinsulinaemia and hyperglycaemia [87]. It has been suggested that adipose tissues play a role in the development of inflammation and the elevation of plasma free fatty acids (FFAs) in obese subjects, which appear to contribute to IR [68].…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…IR is a subnormal biological response to a given concentration of insulin [87] in adipose, muscle, and liver cells [68]. This, for instance, results in the overproduction of glucose by the liver despite fasting hyperinsulinaemia and hyperglycaemia [87]. It has been suggested that adipose tissues play a role in the development of inflammation and the elevation of plasma free fatty acids (FFAs) in obese subjects, which appear to contribute to IR [68].…”
Section: Pathogenesismentioning
confidence: 99%
“…IR is a subnormal biological response to a given concentration of insulin [87] in adipose, muscle, and liver cells [68]. This, for instance, results in the overproduction of glucose by the liver despite fasting hyperinsulinaemia and hyperglycaemia [87].…”
Section: Pathogenesismentioning
confidence: 99%
“…The increased risk of cardiovascular events appears to be related to a large number of factors, including hyperactivation of the reninangiotensin-aldosterone system (RAAS), 1 direct vascular damage caused by hyperglycemia in diabetics, 2 systemic subclinical inflammation, 3 aberrant modulation of adipokine synthesis 4 and a pathological increase in the vascular remodeling rate. 5 Angiotensin II (Ang II), the major actor of the RAAS, acts through two receptor subtypes: Ang II type 1 (AT1R) and type 2 (AT2R).…”
Section: Introductionmentioning
confidence: 99%
“…La diabetes mellitus tipo 2 (DM2) es una enfermedad endocrinológica multifactorial que tiene como manifestación inicial niveles anormalmente elevados de glucosa en sangre, tanto en ayunas como posprandial (1) . Su importancia en salud pública reside en que se constituye como una enfermedad degenerativa crónica que afecta múltiples órganos (ojos, riñones, sistema nervioso periférico y autónomo) siendo la primera causa de ceguera, enfermedad crónica renal terminal y amputaciones en adultos (2) .…”
Section: Introductionunclassified